RADIO KOMUNITAS DAN KEGAGALANNYA SEBAGAI MEDIA COUNTER HEGEMONY (Studi Kasus Pada Radio Panagati dan Angkringan di Yogyakarta) - Eddyono, Aryo Subarkah (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
Community radio is able to offer an alternative that takes the listener impressions, not based on a handful of people or the market desires. It can be called as a medium of resistance counter the hegemony. This research aims to answer the causes of the death of two community radios in Yogyakarta, namely: Radio Panagati and Radio Angkringan. Radio Panagati located in Terban Village  Yogyakarta city, while Radio Angkringan in Timbulharjo Village, Bantul. Both radios are the two pairs of the legendary community radio, especially in Yogyakarta. Based on descriptive-exploratory case study research, the author found that the death of two community radio stations is caused by external factors, including: the rules issued by the state to limit the community radio. External factor has an impact on the community radio’s inability to resolve internal problems that have long existed. If government needs to support community radio, number of rules that burden community radio must be deleted. Keywords:  community radio, counter the hegemony, broadcast democratization.